Hollow fiber supported liquid membrane coupled with high performance liquid chromatography for highly sensitive determination of bisphenols in environmental water samples. Issue 4 (9th January 2015) - Dong, Li-Jie; Tan, Zhi-Qiang; Chen, Ming; Liu, Jing-Fu
Abstract : Hollow fiber supported liquid membrane (HFSLM) extraction provides a high enrichment factor and easy sample clean-up for bisphenols in environmental waters. Abstract : Hollow fiber supported liquid membrane (HFSLM) was applied for the extraction of bisphenols (BPs), including bisphenol S, bisphenol AF, tetramethylbisphenol A, tetrachlorobisphenol A and tetrabromobisphenol A from water samples. The undecane solution of 1.0% (m/v) tri- n -octylphosphine oxide was supported on the pores of the polypropylene hollow fiber membranes (280 μm i.d., 50 μm wall thickness, 0.1 μm pore size, 60 cm length) to form a liquid membrane. The lumen of the hollow fiber membranes was then filled with 0.3 M NaOH as an acceptor to prepare the extraction device, which was placed into a 500 mL water sample (donor) adjusted to pH 4.0 with HCl. After shaking at 200 rpm for 180 min, the acceptor (∼30 μL) was collected and injected into the high performance liquid chromatography system for the determination of the BPs. The proposed HFSLM method provided good enrichment factors (1370–2138), low detection limits (0.1–0.2 μg L −1 ) and good repeatability (RSD = 2.6–8.8%, n = 5). The proposed method was applied to determine the five target BPs in waste water, tap water, river water and lake water samples with satisfactory spiked recoveries (68.6% to 134%) at 0.5 and 1 μg L −1 spiking levels, demonstrating the practicality of the proposed method for the determination of BPs in environmental water samples.